READMISSIONS AFTER DAY CARE SURGERY IN ENT: A TERTIARY CARE EXPERIENCE - Zaman, Shakeel Uz; Faraz, Qazi; Adeel, Mohammad; Suhail, Anwar; Aqil, Shakil (Journal of Ayub Medical College Abbottabad, 2019)
Background: Re-admission following day care surgery in ENT (Ear, Nose & Throat) results in significant morbidity to patient & massive load to hospital & also raises the question on the safety of day care surgery. Only a small number of published studies emphasis on return to hospital within 30 days following day care surgery in otorhinolaryngology especially from our region. This study was carried out to determine the frequency of re-admission after day care surgery in ENT. Methods: We prospectively studied consecutive patients who underwent ENT procedures [i.e., septoplasty, tympanoplasty type I & functional endoscopic sinus surgery (FESS) for deviated nasal septum (DNS), chronic suppurative otitis media tubotympanic (CSOM TT) variety & ethmoidal nasal polyposis (ENP) respectively] as day care surgery case under general anaesthesia at the Section of Otorhinolaryngology and Head & Neck Surgery, Aga Khan University Hospital & Liaquat National Hospital, Karachi from January 2015 to December 2016. All patients aged 20-60 years of both genders were included in the study. SPSS software version 20 was used for data compilation and analysis. p-value less than or equal to 0.05 was taken as significant. Results: In the phase of 24 months, total 317 cases met the inclusion criteria & were included in the study. There were 205 males & 112 females in the study population. One hundred & twenty-two patients having DNS, 128 having CSOM TT & 67 suffering from ENP & underwent septoplasty, tympanoplasty type I & FESS respectively. Complications were observed in a total of 7 (2.2%) patients in our study group & required re-admission within 1 month of surgery. Stratification was done between re-admission & all effect modifiers, with all showing insignificant results. Conclusion: Our results demonstrate that ENT surgeries (septoplasty, tympanoplasty type I & FESS) are safe procedures which can be performed as a day care case with acceptably low re-admission rates. Keywords: Day care; Surgery; Ear; Nose; Tympanoplasty; Nasal surgical procedures